2024
DOI: 10.1038/s41588-023-01640-3
|View full text |Cite
|
Sign up to set email alerts
|

A new genomic framework to categorize pediatric acute myeloid leukemia

Masayuki Umeda,
Jing Ma,
Tamara Westover
et al.

Abstract: Recent studies on pediatric acute myeloid leukemia (pAML) have revealed pediatric-specific driver alterations, many of which are underrepresented in the current classification schemas. To comprehensively define the genomic landscape of pAML, we systematically categorized 887 pAML into 23 mutually distinct molecular categories, including new major entities such as UBTF or BCL11B, covering 91.4% of the cohort. These molecular categories were associated with unique expression profiles and mutational patterns. For… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
11
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 122 publications
2
11
0
Order By: Relevance
“…In particular, UBTF tandem duplications have been characterized as subtype-defining genomic alterations in childhood AML associated with HOX gene dysregulation. 4 , 5 , 11 , 12 Recent studies have now shown that UBTF -TDs are not restricted to pediatric AML but also occur in ∼ 3% of adult AML patients aged 18 to 60 years (median age = 37 years). 9 , 10 UBTF alterations have also recently been described in B-cell acute lymphoblastic leukemia, although these are structural variations leading to focal deletions of exons 18 to 21, resulting in UBTF::ATXN7L3 fusions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In particular, UBTF tandem duplications have been characterized as subtype-defining genomic alterations in childhood AML associated with HOX gene dysregulation. 4 , 5 , 11 , 12 Recent studies have now shown that UBTF -TDs are not restricted to pediatric AML but also occur in ∼ 3% of adult AML patients aged 18 to 60 years (median age = 37 years). 9 , 10 UBTF alterations have also recently been described in B-cell acute lymphoblastic leukemia, although these are structural variations leading to focal deletions of exons 18 to 21, resulting in UBTF::ATXN7L3 fusions.…”
Section: Discussionmentioning
confidence: 99%
“…At the transcriptional level, UBTF -TD AMLs are similar to other well-defined AML subtypes, including NUP98- rearranged ( NUP98- r, ie, NUP98::NSD1 ), NPM1 mutations, DEK::NUP214 , KMT2A- rearranged ( KMT2A -r), and KMT2A partial tandem duplication ( KMT2A- PTD) AMLs. 4 , 12 The similarities in the transcriptional profiles of these AML subtypes suggest a shared mechanism. Similar to AMLs with NPM1 mutations or KMT2A fusion oncoproteins, 16 we demonstrate that UBTF-TD, KMT2A, and menin co-occupy genomic regions that are transcriptionally dysregulated in UBTF -TD leukemias ( Figures 1 and 2 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pediatric acute myeloid leukemia (AML) and myelodysplastic syndrome (MDS) are characterized by unique genetic backgrounds when compared to those in adults. 1-3 Recurrent tandem duplications (TD) of exon 13 of upstream binding transcription factor ( UBTF ) were only recently identified as potential initiating events in pediatric AML, 4-7 accounting for about 4% of newly diagnosed pediatric AML. PCR-based screening covering exon 13 of UBTF also identified UBTF -TD alterations in large adult AML cohorts.…”
Section: Introductionmentioning
confidence: 99%
“…
BRAF mutations occur in approximately 1% of pediatric and adult acute myeloid leukemia (AML) 1,2 and less than 2.5% of acute lymphoblastic leukemia/lymphoma cases. [3][4][5][6] While BRAF mutations are rare in acute leukemias, multiple studies have demonstrated overactivity of the RAS/MAPK signaling pathway.
…”
mentioning
confidence: 99%